2019
DOI: 10.3389/fvets.2019.00110
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasites and the Occurrence of Zoonotic Giardia duodenalis Genotype in Captive Gibbons at Krabokkoo Wildlife Breeding Center, Thailand

Abstract: Intestinal parasitic infections can have an impact on health and growth of wildlife. The current study aims were to determine the prevalence of intestinal parasites and to molecular characterize Giardia duodenalis and Cryptosporidium spp. in captive gibbons at Krabokkoo Wildlife Breeding Center, Thailand. Fifty-five gibbons, 2 agile- ( Hylobates agilis ), 38 lar- ( Hylobates lar ) and 15 pileated gibbons ( H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Cryptosporidium infection rates have been typically reported in the range of 3-6% in NHP species including baboons, gibbons, macaques, and orangutans (41,(43)(44)(45)(46)(47)(48). Other surveys failed to detect the parasite in their captive NHP collections (13,29,(49)(50)(51)(52)(53). This variability is clearly reflected in the present study, where an overall Cryptosporidium infection rate of 1.0% was found, but the parasite was only detected in two of the six participating zoological institutions.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Cryptosporidium infection rates have been typically reported in the range of 3-6% in NHP species including baboons, gibbons, macaques, and orangutans (41,(43)(44)(45)(46)(47)(48). Other surveys failed to detect the parasite in their captive NHP collections (13,29,(49)(50)(51)(52)(53). This variability is clearly reflected in the present study, where an overall Cryptosporidium infection rate of 1.0% was found, but the parasite was only detected in two of the six participating zoological institutions.…”
Section: Discussionsupporting
confidence: 49%
“…Our genetic analyses revealed that eight out of 10 G. duodenalis infections were caused by the assemblage B of the parasite, and that all the genetic variants detected (sub-assemblages AI, AII, and BIV) were zoonotic (70). This predominance of assemblage B over assemblage A has been confirmed in other NHP populations from Belgium and the Netherlands (71), China (72)(73)(74), Croatia (65), Italy (66), the Republic of Congo (49), Slovakia (67), Sweden (75), and Thailand (52). However, it should be noted that this trend is far from general, and the opposite result (preponderance of assemblage A over assemblage B) has also been reported in captive NHP belonging to the genera Alouatta and Ateles in Brazil (76,77) and in different NHP collections from Spanish zoological gardens (13,68).…”
Section: Discussionmentioning
confidence: 64%
“…Humans and many animals are important reservoirs for Cryptosporidium spp. and G. duodenalis , and large amounts of both pathogens and extremely high oocyst and cyst excretions have been traced in their feces ( Graczyk & Fried, 2007 ; Tangtrongsup et al, 2019 ). Moreover, the transmission of these parasites occurs through a variety of mechanisms in the fecal-oral route, including the direct contact with or indirect ingestion of contaminated food or water ( Castro-Hermida et al, 2009 ; Dixon, 2016 ; Saaed & Ongerth, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Humans and many animals are important reservoirs for Cryptosporidium spp. and G. duodenalis, and large amounts of both pathogens and extremely high oocyst and cyst excretions have been traced in their feces (Graczyk & Fried, 2007;Tangtrongsup et al, 2019). Moreover, the transmission of these parasites occurs through a variety of mechanisms in the fecal-oral route, including the direct contact with or indirect ingestion of contaminated food or water (Castro-Hermida et al, 2009;Dixon & Brent, 2016;Saaed & Ongerth, 2019).…”
Section: Introductionmentioning
confidence: 99%